PERBEDAAN KADAR TRIGLISERIDA ANTARA ANGGOTA SENAM BODY LANGUAGE DENGAN ANGGOTA SENAM HIGH IMPACT SETELAH PEMBERIAN ASUPAN MAKANAN YANG SEBELUMNYA MELAKUKAN SENAM BODY LANGUAGE DAN SENAM HIGH IMPACT - Dewi Kurniawati; Ambrosius Purba; Nur Siti Fatimah (PAIFORI, 2018)
The majority of studies have found that aerobic exercise can reduce the increment of triglyceride postprandial in plasma. Therefore, the author is doing this research to know the difference of triglyceride concentration in plasma between-group who joint high impact exercise and group who joint body language exercise after given the same amount and dietary composition which had done high impact and body language exercise before. Twenty men (19-39 years old) did high impact or body language exercises for 1 hour. Two hours later, they were given dietary composition with carbohydrates 60% and fat 25%. Then the triglyceride postprandial concentrations were measured 3, 5, and 6 hours after the given dietary food. The result showed that the triglyceride concentration of high impact group was higher than body language group 3 hours after given dietary food (122.167 ± 17.11627 vs 111.67± 7.86554 mg/dL) and there was no difference between the high impact and body language group 5 hours (96.167 ± 7.25029 vs 94.0 ± 16.66133mg/dL) and 6 hours after given dietary food (77.5 ± 8.8261 vs 78.167 ± 14.27469 mg/dL).In conclusion, the triglyceride concentration of the high impact group was higher than the body language group 3 hours after given the same amount and dietary composition. But, there was no difference between triglycerides concentration of body language group and high impact group 5 and 6 hours after given the same amount and dietary composition which had done high impact and body language exercise before.